2022
DOI: 10.1515/biol-2022-0103
|View full text |Cite
|
Sign up to set email alerts
|

BTBD10 inhibits glioma tumorigenesis by downregulating cyclin D1 and p-Akt

Abstract: The aim of this study was to investigate the role of BTBD10 in glioma tumorigenesis. The mRNA and protein levels of BTBD10 in 52 glioma tissues and eight normal brain tissues were determined using reverse transcription polymerase chain reaction (RT-PCR) and western blot analysis, respectively. U251 human glioblastoma cells were infected with BTBD10-expressing or control lentiviruses. Cell growth was evaluated using the methyl thiazolyl tetrazolium (MTT) assay. Cell apoptosis and cell cycle distribution were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The miRNAs promote the degrading and inhibiting translation of mRNA by interacting with their 5′ and 3′ untranslated region (UTR) sequences. Our results showed that TGFBR1 [ 30 ], SUPT6H [ 31 ], CNOT6L [ 32 ], and BTBD10 [ 33 ], which were reported to participate in the regulation of cell apoptosis and follicular development, may be the key target genes for miR-202-5p to regulate goose GCs. Subsequently, the result of qRT-PCR indicates that miR-202-5p impacted the expression of BTBD10 most significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs promote the degrading and inhibiting translation of mRNA by interacting with their 5′ and 3′ untranslated region (UTR) sequences. Our results showed that TGFBR1 [ 30 ], SUPT6H [ 31 ], CNOT6L [ 32 ], and BTBD10 [ 33 ], which were reported to participate in the regulation of cell apoptosis and follicular development, may be the key target genes for miR-202-5p to regulate goose GCs. Subsequently, the result of qRT-PCR indicates that miR-202-5p impacted the expression of BTBD10 most significantly.…”
Section: Discussionmentioning
confidence: 99%